Religious Moderation Model in the Independent Student Exchange Program Through the Nusantara Module (Research in the Islamic Religious Education Study Program at Garut University) - Nenden Munawaroh; Ijudin; Shelsya Azzahra Indriani (al-Afkar, Journal For Islamic Studies, 2024)
Students participating in the Merdeka Student Exchange program are required to take the Nusantara Module course. Through a series of activities, the Nusantara Module seeks to expose the diversity that exists in the archipelago and concentrate on developing a thorough understanding. This research aims to find out how the Nusantara Module contributes to the cultivation of students' religious moderation attitudes. Through the Nusantara Module, this study attempts to investigate the paradigm of religious moderation within the framework of the Merdeka Student Exchange Program. with a research focus on Inbound students at Garut University. Through a qualitative approach, this study collected data from interviews, observations, and document analysis related to the implementation of the program. The results of the study show that the Nusantara module, the implementation of the Nusantara Module begins with the existence of a policy from the University, embodied in the study program curriculum, providing space for students to participate in the PMM program and the Nusantara module. The principles of religious moderation built in the Nusantara module include: Tawasuth, tasammuh, The impact of changes in student attitudes not only enriches students' insights about religious and cultural diversity in Indonesia, but also succeeds in building an attitude of tolerance and moderation among students. These findings are expected to be a reference in curriculum development that is more inclusive and responsive to the social dynamics of religion.